Cape Verde, Namibia, and Kingdom of Swaziland : Selected Issues Paper on the Challenges of Small Middle-Income Countries in Sub-Saharan Africa. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper focuses on the challenges of small middle-income countries (MIC) in sSub-Saharan Africa (SSA) comprising Cape Verde, Namibia, and the Kingdom of Swaziland. The IMF report summarizes the analytic underpinnings that support the IMF staff's advice on policies to strengthen macroeconomic stability, foster more inclusive growth, and enhance the resilience of their financial systems. It recommends that macroeconomic policies should aim to rebuild policy buffers to help cushion against large external shocks especially given the prevalence of pegged exchange rate regimes in these economies.